A Simple Iron-Catalyst for Alkenylation of Ketones Using Primary Alcohols - Motahar Sk; Ashish Kumar; Jagadish Das; Debasis Banerjee (Molecules, 2020)
Herein, we developed a simple iron-catalyzed system for the α-alkenylation of ketones using primary alcohols. Such acceptor-less dehydrogenative coupling (ADC) of alcohols resulted in the synthesis of a series of important α,β-unsaturated functionalized ketones, having aryl, heteroaryl, alkyl, nitro, nitrile and trifluoro-methyl, as well as halogen moieties, with excellent yields and selectivity. Initial mechanistic studies, including deuterium labeling experiments, determination of rate and order of the reaction, and quantitative determination of H2 gas, were performed. The overall transformations produce water and dihydrogen as byproducts.